2014
DOI: 10.1159/000360479
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Improvement of Speech Perception with the Fine Structure Processing Coding Strategy in Cochlear Implants

Abstract: Aims: To investigate the long-term effects of the fine structure processing (FSP) coding strategy on speech perception in noise and quality of life in experienced cochlear implant (CI) users. Methods: In a prospective comparative clinical trial, 32 experienced postlingually deafened CI recipients were upgraded from the Tempo+ to the Opus 2 audio processor, implementing FSP in one group and high-definition continuous interleaved sampling (HDCIS) coding strategy in another group with identical frequency ranges. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Studies have suggested that bilateral CI listeners benefit from the FSP stimulation strategy in a speech discrimination test in noise (12)(13)(14)(15)(16), especially for native speakers of tonal languages (17)(18)(19). Dorman et al (20) studied sound localization in FSP and CIS bilateral users and did not find differences between subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that bilateral CI listeners benefit from the FSP stimulation strategy in a speech discrimination test in noise (12)(13)(14)(15)(16), especially for native speakers of tonal languages (17)(18)(19). Dorman et al (20) studied sound localization in FSP and CIS bilateral users and did not find differences between subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…After 12 months of listening experience, the FSP coding strategy group showed a significant improvement in speech perception in noise while the HDCIS group showed no difference. In a follow-up study, Kleine Punte, De Bodt and Van de Heyning (2014) reported an improvement in the FSP coding strategy group after 24 months of listening experience, while the HDCIS coding strategy group did not show a significant difference. It is possible that extended listening experience, beyond the 6-month interval evaluated here, may be needed to benefit from electrically represented fine structure information.…”
Section: Discussionmentioning
confidence: 94%
“…Seebens and Diller [13] revealed similar result in their study about upgrading form TEMPO+ to OPUS 2 speech processor. In the long-term follow up study about upgrading to speech processor with newer coding strategy, subjects with newer speech processor revealed better performance [14]. As above mentioned, there is no documented analysis of the impact of the whole system upgrade on speech performance.…”
Section: Discussionmentioning
confidence: 99%